2017
DOI: 10.1097/meg.0000000000000751
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of sedation with midazolam–ketamine versus propofol–fentanyl during endoscopy in children: a randomized trial

Abstract: PurposeWe aimed to compare the efficacy and safety of midazolam plus ketamine versus fentanyl plus propofol combination administered to children undergoing upper gastrointestinal endoscopy (UGE) and to determine the most appropriate sedation protocol.Materials and methodsThis prospective, randomized, single-blind study included patients between the ages of 4 and 17 years who underwent UGE for diagnostic purposes. Patients were divided randomly into groups A (midazolam–ketamine combination, n=119) and B (fentan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 41 publications
1
28
0
1
Order By: Relevance
“…25 patients had score of six, 15 minutes after stopping ketamine infusion whereas in Group B, 30 patients had score of six, 5 minutes after stopping propofol infusion, similar results were shown by Akbult et al that recovery time was less in propofolfentanyl combination. (28) Similar to Irwin MG et al study, it was observed that the patients were calm and quiet at the score of six in Group B. (13) In Group A, 46 patients were fit for discharge within two hours of completion of procedure and out of the 4 patients who were not discharged, 3 patients had severe emergence delirium so they were given sedation by injection diazepam and so could not be sent home.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…25 patients had score of six, 15 minutes after stopping ketamine infusion whereas in Group B, 30 patients had score of six, 5 minutes after stopping propofol infusion, similar results were shown by Akbult et al that recovery time was less in propofolfentanyl combination. (28) Similar to Irwin MG et al study, it was observed that the patients were calm and quiet at the score of six in Group B. (13) In Group A, 46 patients were fit for discharge within two hours of completion of procedure and out of the 4 patients who were not discharged, 3 patients had severe emergence delirium so they were given sedation by injection diazepam and so could not be sent home.…”
Section: Discussionmentioning
confidence: 55%
“…(1) Akbult et al in their study concluded that in upper gastrointestinal endoscopic procedures midazolam-ketamine combination was comfortable as compared to propofol-fentanyl combination but propofolfentanyl combination had fewer side effects. (28) In both the Groups, recovery of patients was assessed by modified Steward Coma Score, maximum of six. It was seen that points comprising recovery in consciousness level were less in Group A as compared with Group B, than the points comprising the recovery in airway and activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, as regarding the associated side effects, they found a significantly higher prevalence of nausea and vomiting in group PK (53.8%) in comparison to group PF (32.3%) (p=0.013). This can be explained by the higher incidence of vomiting in gastrointestinal procedures than in others [3]. Respiratory complications during recovery as bronchospasm, cough, stridor, and Laryngospasm were significantly higher in group PK (9%) in comparison to group PF (2%) (p=0.024).…”
Section: Discussionmentioning
confidence: 94%
“…Upper gastrointestinal endoscopy procedures in pediatric patients for diagnostic and therapeutic purposes have increased and become more frequent [3]. Choosing a sedative should be on the basis of its onset time, associated adverse effects and time to restore cognitive function after stopping it [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation